Stretchable Sweat‐Activated Battery in Skin‐Integrated Electronics for Continuous Wireless Sweat Monitoring - Liu, Yiming; Huang, Xingcan; Zhou, Jingkun; Yiu, Chun Ki; Song, Zhen; Huang, Wei; Nejad, Sina Khazaee; Li, Hu; Wong, Tsz Hung; Yao, Kuanming; Zhao, Ling; Yoo, Woojung; et al. (Advanced science, 2022)
Wearable electronics have attracted extensive attentions over the past few years for their potential applications in health monitoring based on continuous data collection and real‐time wireless transmission, which highlights the importance of portable powering technologies. Batteries are the most used power source for wearable electronics, but unfortunately, they consist of hazardous materials and are bulky, which limit their incorporation into the state‐of‐art skin‐integrated electronics. Sweat‐activated biocompatible batteries offer a new powering strategy for skin‐like electronics. However, the capacity of the reported sweat‐activated batteries (SABs) cannot support real‐time data collection and wireless transmission. Focused on this issue, soft, biocompatible, SABs are developed that can be directly integrated on skin with a record high capacity of 42.5 mAh and power density of 7.46 mW cm−2 among the wearable sweat and body fluids activated batteries. The high performance SABs enable powering electronic devices for a long‐term duration, for instance, continuously lighting 120 lighting emitting diodes (LEDs) for over 5 h, and also offers the capability of powering Bluetooth wireless operation for real‐time recording of physiological signals for over 6 h. Demonstrations of the SABs for powering microfluidic system based sweat sensors are realized in this work, allowing real‐time monitoring of pH, glucose, and Na+ in sweat. A stretchable, conformable sweat‐activated battery (SAB) has been developed with high power density (7.46 mW cm−2) and energy capacity (42.5 mAh); it enables lighting 120 lighting emitting diodes (LEDs) for 5 h, and offers enough power to support Bluetooth wireless operation for real‐time recording of physiological signals in state‐of‐art wearable sensors for over 6 h. The SAB is also demonstrated in powering microfluidic system based sweat sensors for real‐time monitoring of pH, glucose, and Na+ in sweat.